Radiological features of body packers: An experience from a regional accident and emergency department in close proximity to the Hong Kong International Airport. Issue 4 (July 2018) - Tsang, Ho Kai Patrick; Wong, Cheuk Kei Kathy; Wong, Oi Fung; Chan, Wing Lun William; Ma, Hing Man; Lit, Chau Hung Albert
Background: Body packing is a frequently used method for drug trafficking. Local information about the clinical and radiological features of body packing is lacking. Objectives: To evaluate the radiological features of body packers presenting to a hospital near to the Hong Kong International Airport and to compare the radiological features of solid form versus liquid cocaine. Methods: This was a retrospective cohort study. Medical notes of 269 suspected body packers, presenting to the Accident and Emergency Department of North Lantau Hospital under the detention by the law enforcement personnel from 1st January 2015 to 28th February 2017, were reviewed. The radiological features of body packing were retrospectively evaluated. Results: Sixty-nine cases were confirmed body packers radiographically. Majority of them (81%, 56/69) were cocaine packers. Powder form cocaine (67%, 49/69) was the most popular drug packed, followed by liquid cocaine (15%, 10/69). There was a trend of increasing incidence of liquid cocaine packers. The classical 'double condom', 'tic tac' and 'halo' signs were present in 94%, 72.5% and 42% of cases with radiologically confirmed body packing respectively. The 'rosette' sign was only identified in 1 case. Three new radiological signs, the 'bag of eggs', 'lucent triangle' and 'black crescent' sign, were suggested to aid identification of drug packets. The classical 'tic tac' sign was absent in all liquid cocaine packing cases (p<0.05). The liquid cocaine packets appeared irregular with indistinct border in majority of cases (p<0.05). The solid form packets were mostly opaque to faeces while liquid cocaine had variable density (p<0.05). Most solid form packets had homogeneous content which was in contrast to the heterogeneous content in liquid cocaine (p<0.05). Conclusion: Failure in detecting drug body packing may result in medicolegal consequences. Emergency physicians need to be aware of subtle radiological signs of liquid cocaine packets in the plain abdominal radiography.